“Strange Beasts… in taste Chinese” : Le goût chinois dans l’Angleterre du XVIIIe siècle ou l’esthétique de l’étrange - Vanessa Alayrac (Revue LISA)
The wonders and riches of China brought back to England by the East Indiamen at the end of the 17th century and in the 18th century triggered a deep interest for things Chinese. Indeed, England was hit by the Chinese taste in the decorative arts, emblematised by the playful chinoiserie style. This taste nonetheless evolved during the 18th century, and although it remained very popular throughout the period, it underwent some sharp criticisms. What was the nature of the English reception of this style? Why was it so welcomed, and at the same time seen so suspicious? This paper explores the ambivalence which lay in the reception of the Chinese style, and examines what was perceived as the lure and threat of Chinese exoticism through the concepts of strangeness and foreignness.